Peningkatan Pemahaman Masyarakat Mengenai Penggunaan Antibiotik untuk Cegah Resistensi di Kampung Rawa Panjang - Mulki, Munir Alinu; Sholih, Mally Ghinan; Utami, Marsah Rahmawati; Siboro, Dewi Pratiwi Purba (Kolaborasi Masyarakat, 2025)
Antibiotics are substances or compounds that are either synthetically produced or naturally generated by microorganisms, especially fungi. They are used as inhibitors of other microorganisms. The use of antibiotics in humans is based on their minimal toxicity to the human body. Inaccurate and prolonged use of antibiotics can lead to the development of resistance. A step taken to minimize antibiotic resistance is the introduction of the 2023 PITIK (Penyuluhan Informasi Tentang Antibiotik) program. Thirty-three participants from the community around Kampung Rawa Panjang, Gang Pemuda, RT 01/RW 05, Kota Bekasi, attended this antibiotic education program. Education for the community was conducted using a cross-sectional approach and a questionnaire as an instrument. The results of questionnaire data analysis show that public understanding of the definition, how it works, side effects, how to purchase and how to use antibiotics correctly increased from 27.3% to 93.9%. Therefore, it can be concluded that this education program helps improve public awareness of the proper use of antibiotics.